Aortic pulsatility index predicts clinical outcomes in heart failure: a sub‐analysis of the ESCAPE trial. (17th February 2021) - Belkin, Mark N.; Alenghat, Francis J.; Besser, Stephanie A.; Nguyen, Ann B.; Chung, Ben B.; Smith, Bryan A.; Kalantari, Sara; Sarswat, Nitasha; Blair, John E.A.; Kim, Gene H.; Pinney, Sean P.; Grinstein, Jonathan
Abstract: Aims: Aortic pulsatility index (API), calculated as (systolic–diastolic blood pressure)/pulmonary capillary wedge pressure (PCWP), is a novel haemodynamic measurement representing both cardiac filling pressures and contractility. We hypothesized that API would better predict clinical outcomes than traditional haemodynamic metrics of cardiac function. Methods and results: The Evaluation Study of Congestive Heart Failure and Pulmonary Artery Catheterization Effectiveness (ESCAPE) trial individual‐level data were used. Routine haemodynamic measurements, including Fick cardiac index (CI), and the advanced haemodynamic metrics of API, cardiac power output (CPO), and pulmonary artery pulsatility index (PAPI) were calculated after final haemodynamic‐monitored optimization. The primary outcome was a composite endpoint of death or need for orthotopic heart transplant (OHT) or left ventricular assist device (LVAD) at 6 months. A total of 433 participants were enrolled in the ESCAPE trial of which 145 had final haemodynamic data. Final API measurements predicted the primary outcome, OR 0.47 (95% CI 0.32–0.70, P <  0.001), while CI, CPO, and PAPI did not. Receiver operator characteristic analyses of final advanced haemodynamic measurements indicated API best predicted the primary outcome with a cutoff of 2.9 (sensitivity 76.2%, specificity 55.3%, correctly classified 61.4%, area‐under‐the‐curve 0.71), compared with CPO, CI, and PAPI. Kaplan–Meier analyses indicated API ≥ 2.9 was associated with greater freedom from the primary outcome (83.5%), compared with API < 2.9 (58.4%), P =  0.001. While PAPI was also significantly associated, CI and CPO were not. Conclusions: The novel haemodynamic measurement API better predicted clinical outcomes in the ESCAPE trial when compared with traditional invasive haemodynamic metrics of cardiac function.